Features of the Development of the Russian Language in the Era of Globalization (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article discusses the main difficulties that arise when teaching first-year non-philology students whose native language is Uzbek. Knowledge of the distinctive features of the phonetic system and morphology of the Uzbek language allows you to select the necessary exercises and correctly organize learning activities in classes in Russian as a foreign language. It is also important to teach official business and scientific styles of speech, as well as to develop skills in producing a monologue.